Association between ambient fine particulate matter and hemorrhagic stroke in Yancheng, China - Kai Qian; Xiaorong Xu; Chunxiang Xu; Yuanfeng Jiao; Qian Sun; Xiaofeng Yu; Lingzheng Sun (Frontiers in Public Health, 2026)
Objectives Ambient air pollution, particularly fine particulate matter (PM 2.5 ), has been linked to cerebrovascular disease. However, findings on the short-term effects of PM 2.5 exposure on hemorrhagic stroke (HS) have been inconsistent across studies. Therefore, this study investigated the association between short-term PM 2.5 exposure and HS hospitalization in Yancheng, China. Methods An individual-level time-stratified case-crossover study was conducted using hospitalization records of patients with HS from four major hospitals in Yancheng between 2022 and 2024. Conditional logistic regression models were applied to estimate the associations between short-term PM 2.5 exposure and HS hospitalization across different lag structures. Stratified analyses were further performed according to sex, age, hypertension, diabetes, smoking, alcohol consumption, and season. Results A total of 2,312 patients hospitalized for HS were included in the analysis. The strongest association was observed at lag01, where each 10 μg/m 3 increase in PM 2.5 concentration was associated with a 3.24% increase in HS hospitalization (95% CI: 0.55%−6.00%). Significant increases were also observed at lag0 and lag1, with corresponding effect estimates of 2.50% (95% CI: 0.11%−4.95%) and 2.76% (95% CI: 0.32%−5.27%), respectively. The associations remained significant after adjustment for ozone (O 3 ) but were no longer statistically significant after adjustment for sulfur dioxide (SO 2 ), nitrogen dioxide (NO 2 ), and carbon monoxide (CO). Relatively stronger effect estimates were observed among females, older adults, individuals with hypertension or diabetes, smokers, alcohol consumers, and during the cold season. Conclusion Short-term PM 2.5 exposure was associated with an increased risk of HS hospitalization in Yancheng, China, with the strongest effects observed within the first two days after exposure. The associations were more pronounced among susceptible populations and during the cold season.